Effects of precipitation changes on the dynamics of sparse elm woodland in Northeastern China - Tang, Yi (2018)
Elm (Ulmus pumila L.) is the dominant tree species in the sparse elm woodland, the original vegetation in the Horqin Sandy Land. The effects of changes in precipitation on U. pumila trees have not been fully studied. We determined a dynamic model by considering the five stages in the U. pumila life cycle, i.e. seed, seedling, and juvenile, mature and over-mature tree stages. The effects of changes in precipitation on population density and age structure were then evaluated. Population density, after averaging all study developmental morphology stages, ranged from 16.67 individuals/m2 to 25.01 individuals/m2 under a mean annual precipitation (MAP) of 80% to 120%, respectively. This suggests that population density could increase as MAP also increased. The proportion of seedlings, and juvenile, mature and over-mature trees were 95.23%, 4.58%, 0.19% and 0.01%, respectively, under all precipitation levels. Thisindicates that precipitation had little effects on the developmental stages of the studied U. pumila populations in the Horqin Sandy Land. Additional water supply might be provided in addition to the natural rainfall that occurs in theregion, for contributing to maintain U. pumila population density in the Horqin Sandy Land.